Finger Vein Recognition Algorithm Using Phase Only Correlation. - Mahri, Nurhafizah; Azmin Sundi, Shahrel; Rosdi, Bakhtiar Affendi (2010)
In this paper, we propose an algorithm for finger vein recognition with less complexity in the image preprocessing phase, where finger vein pattern extraction is not included at all.